2023
DOI: 10.1002/dro2.46
|View full text |Cite
|
Sign up to set email alerts
|

Bionic surface diode for droplet steering

Abstract: Control of droplet sliding and its interfacial behavior such as sliding resistance and friction have important applications in microfluidic and energy-related fields. Nature provides many examples of interface-driven droplet sliding control; yet, to date, the continuous governing of the multiphase process and precise steering of droplet sliding remain challenging. Here, directional-dependent ultraslippery patterned surfaces with significant droplet sliding anisotropy were created by coordinating the heterogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…Emulating the surfaces of living organisms in nature and exploring the mysterious surface properties are hot research topics in the area of surface and interface. 66,67 These engineered surfaces are generally complex and fine-structured, which makes it challenging to prepare them with traditional material processing methods. AM, with its high degree of design freedom and fabrication flexibility, is increasingly playing an irreplaceable role in the field of material surface and interface.…”
Section: Droplet Interface Prepared By Ammentioning
confidence: 99%
See 1 more Smart Citation
“…Emulating the surfaces of living organisms in nature and exploring the mysterious surface properties are hot research topics in the area of surface and interface. 66,67 These engineered surfaces are generally complex and fine-structured, which makes it challenging to prepare them with traditional material processing methods. AM, with its high degree of design freedom and fabrication flexibility, is increasingly playing an irreplaceable role in the field of material surface and interface.…”
Section: Droplet Interface Prepared By Ammentioning
confidence: 99%
“…Emulating the surfaces of living organisms in nature and exploring the mysterious surface properties are hot research topics in the area of surface and interface 66,67 . These engineered surfaces are generally complex and fine‐structured, which makes it challenging to prepare them with traditional material processing methods.…”
Section: Droplet Interface Prepared By Ammentioning
confidence: 99%
“…For instance, Leng et al summarize the mechanisms of water droplet manipulation on various biological surfaces. Yang et al explored multi-bioinspired SLIPS-patterned surfaces that allow for directional droplet sliding, and precise steering of droplet friction was created by coordinating the heterogeneous wettability of the back of the desert beetle, directional-dependent architecture of the butterfly wing, and ultraslippery configuration of N. alata.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Leng et al 15 summarize the mechanisms of water droplet manipulation on various biological surfaces. Yang et al 16 explored multi-bioinspired SLIPS-patterned surfaces that allow for directional droplet sliding, and precise steering of droplet friction was created by coordinating the heterogeneous wettability of the back of the desert beetle, directional-dependent architecture of the butterfly wing, and ultraslippery configuration of N. alata . Yang et al 17 reported three-dimensional (3D) topological SLIPS with an anisotropic-slippery-Wenzel state; fabricated rice leaflike grooved nanotextured SLIPS can properly shape the droplet footprint to achieve a sliding resistance anisotropy of 109.8 μN.…”
Section: Introductionmentioning
confidence: 99%
“…Aizenberg et al developed a slippery-liquid-infused porous surface (SLIPS) inspired by Nepenthes, which has gained considerable attention . Owing to its excellent slippery performance, SLIPS shows application prospects in various fields, including anti-icing, corrosion resistance, antifouling, droplet transportation, and fog collection. …”
Section: Introductionmentioning
confidence: 99%